2019
DOI: 10.1016/j.ssmph.2018.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Low birth weight and maternal incarceration in pregnancy: A longitudinal linked data study of Western Australian infants

Abstract: RationaleImproved birth weight outcomes have been reported for infants of mothers imprisoned during pregnancy relative to similarly disadvantaged mothers, however, findings are equivocal and evidence is lacking from jurisdictions outside the United States.ObjectiveTo investigate whether maternal imprisonment during pregnancy is a determinant of low birth weight (<2500 g) for Indigenous and non-Indigenous infants in Western Australia.MethodsA longitudinal sample of 41,910 singleton infants born in Western Austr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…First, one study used linked medical records, and found babies born to women incarcerated during pregnancy were at an increased likelihood to be LBW, pre‐term, and re‐admitted to the hospital after birth compared to community controls (Walker et al, 2014). Dowell et al (2019) found that maternal imprisonment before or during pregnancy remained associated with infant LBW even after adjusting for significant pregnancy risks.…”
Section: Resultsmentioning
confidence: 99%
“…First, one study used linked medical records, and found babies born to women incarcerated during pregnancy were at an increased likelihood to be LBW, pre‐term, and re‐admitted to the hospital after birth compared to community controls (Walker et al, 2014). Dowell et al (2019) found that maternal imprisonment before or during pregnancy remained associated with infant LBW even after adjusting for significant pregnancy risks.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with global figures, the number of women in prison in Australia has increased by 62% (3,292) compared to 2,030 in 2011, while Indigenous women make up 30% of the female prison population (Australian Bureau of Statistics [ABS], 2021 ). Though research on impact of maternal incarceration and mothering in prison is robust (e.g., Casey-Acevedo et al, 2004 ; Dowell et al, 2019 ; Goshin et al, 2014 ; Nuytiens & Jehaes, 2022 ), imprisoned mothers’ voices are rarely considered in such research. Mothers’ perspectives about the effectiveness of prison-based programs, including parenting programs, prison nursery programs, or health programs have been investigated (Bard et al, 2016 ; Kennedy et al, 2020 ;; Walker et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Newborn babies and infants who were separated from their mothers experienced a disruption in their attachment and had elevated internalising and externalising problems, compared to those who were not separated (Fritz & Whiteacre, 2016 ; Poehlmann‐Tynan & Turney, 2021; Poehlmann 2005 ). Analyses of a linked administrative dataset from Australia revealed that children exposed to maternal imprisonment had higher infant mortality rates, increased risk of developmental vulnerabilities, and were twice as likely to encounter child protection services by the age of two, compared to children of mothers with no involvement in the correctional system (Dowell et al, 2018 , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Com relação ao peso ao nascer, os resultados obtidos relativos à idade materna estão de acordo com a literatura científica, pois estudos com essa temática relacionam o aumento do peso das crianças ao aumento da idade materna, com relação inversa apenas nos extremos de idade. (19)(20)(21) Sobre o número de consultas pré-natais, pode estar relacionado à maior duração da gestação, visto que quanto mais prolongada, mais consultas são agendadas, sendo que a partir de 36 semanas de gestação estão indicados, pelo menos, retornos semanais. (22) Sobre o peso aos seis e doze meses, a associação positiva com a estatura ao nascer também foi encontrada em dois estudos realizados no estado de Minas Gerais, em que as crianças que apresentavam maior comprimento ao nascer apresentaram maior velocidade de ganho de peso nos primeiros seis (23) ou doze meses de vida.…”
Section: Discussionunclassified